Is there a dominant leg in cross-country skiers? - Ebru, C.; Imdat Y. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: There are many factors that may affect the performance of cross-country skiers [1]. Years ago, we were sure the most important performance determining parameter was maximal oxygen consumption [2]. However, the fact that the diversity of competition has increased to the present, and in particular, that sprint races have become widespread has resulted in certain changes in this consideration of ours. The increase in the speed factor in races led strength and speed to gain importance among motoric abilities [3]. Other than performance, the strength parameter is also quite important in the increase of balance and in the minimization of the risk of injury [4]. The aim of this study is to examine the dominant leg strengths of the athletes who have been involved in skiing for more than 10 years.